Inspection and polypectomy during both insertion and withdrawal or only during withdrawal of colonoscopy?: A protocol for systematic review and meta analysis. Issue 27 (2nd July 2020) - Wei, Yaping; Shen, Guofan; Yang, Yutong; Jin, Zheng; Hu, Wei; Zhu, Ying
Abstract: Introduction: Current evidence supporting additional inspection and polypectomy during insertion of colonoscopy is limited. We plan to provide a systematic review and meta-analysis to compare the yield of inspection and polypectomy during both insertion and withdrawal versus the traditional practice of inspection and polypectomy during withdrawal only. Methods and analysis: Randomised controlled trials evaluating inspection and polypectomy during both insertion and withdrawal versus inspection and polypectomy during withdrawal only will be searched in MEDLINE, EMBASE, Web of Science, the Cochrane Library, ClinicalTrials.gov, and Google Scholar, from database inception to 31 May 2020. Data on study design, participant characteristics, and outcomes will be extracted. Primary outcomes to be assessed are adenoma detection rate. Secondary outcomes include polyp detection rate, advanced adenoma detection rate, the mean number of adenomas per patient, polyp miss rate, the mean number of adenomas per colonoscopy, procedure duration, cecal intubation rate, procedure difficulty, patient discomfort, sedation dose, and adverse events. Study quality will be assessed using the Cochrane Risk of Bias Tool. Meta-analysis will be performed using RevMan V.5.3 statistical software. Data will be combined with random effect model. The results will be presented as a risk ratio (RR) for dichotomous data, and weighted/standard mean difference for continuous data. Publication bias will be visualized using funnel plots. Ethics and dissemination: This study will not use primary data, and therefore formal ethical approval is not required. The findings will be disseminated through peer-reviewed journals and committee conferences. Protocol registration number: INPLASY202050051. Abstract : Supplemental Digital Content is available in the text